Contextos domésticos en Cartagena (SS. III a.C. al IX d.C.): procesos de cambio y continuidad. - Gómez Marín, Javier; Vizcaíno Sánchez, Jaime; Noguera Celdrán, José Miguel; Madrid Balanza, María José; García-Aboal, Victoria; Velasco Estrada, Víctor (Instituto de Arqueología de Mérida, 2024)
The archaeological record of Cartagena provides remarkable information on the resilient nature of the city’s domestic areas between Antiquity and the Early Middle Ages. Between the end of the 3rd century B.C. and the 9th century A.D., large areas of the urban site were developed for domestic and domestic-craft habitat, which underwent profound transformation processes with the passing of time. There are also areas of a public or semi-public nature that were converted over time into domestic and craft areas. This paper analyses these contexts and explains the dynamics of strong processes of continuity and change experienced by their domestic units or by other public and semi- public buildings that were transformed into residential ones.
http://www.iam.csic.es/es/publicaciones
Keywords: Arquitectura doméstica - Cartagena (Murcia); Cartagena (Murcia) - Restos arqueológicos; Arquitectura doméstica; Etapa púnica; Etapa romana; Etapa tardía; Etapa islámica